2010
DOI: 10.3113/fai.2010.0994
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Pressure During Running in Subjects With Chronic Ankle Instability

Abstract: Clinicians treating patients with CAI should consider providing interventions to decrease the amount of rearfoot inversion at FS and during loading in order to create a more medial COP trajectory upon impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 46 publications
6
47
2
2
Order By: Relevance
“…51 Schmidt et al 49 found that individuals with CAI also exhibited slower loading responses of the lateral and medial rearfoot and the medial midfoot during jogging. When comparing individuals with CAI and individuals who sustained isolated ankle sprains but had no subsequent feelings of instability during running, Morrison et al 16 showed that individuals with CAI presented with a more lateral COP of the rearfoot at foot strike and a more lateral COP trajectory during loading. Both the lateral COP and slower loading responses could suggest that a neuromuscular response occurs in individuals with CAI to maintain a functional ''close-packed'' supinated position of the subtalar and midfoot joints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Schmidt et al 49 found that individuals with CAI also exhibited slower loading responses of the lateral and medial rearfoot and the medial midfoot during jogging. When comparing individuals with CAI and individuals who sustained isolated ankle sprains but had no subsequent feelings of instability during running, Morrison et al 16 showed that individuals with CAI presented with a more lateral COP of the rearfoot at foot strike and a more lateral COP trajectory during loading. Both the lateral COP and slower loading responses could suggest that a neuromuscular response occurs in individuals with CAI to maintain a functional ''close-packed'' supinated position of the subtalar and midfoot joints.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have identified specific deficits in proprioception, 10,11 peroneal reaction time, 12,13 and postural control 14,15 in individuals with CAI. Alterations in lower extremity kinematics during gait [16][17][18][19] and jump landings 20,21 also are evident in individuals with CAI, whereas strength deficits are controversial. [22][23][24][25][26] It is unclear whether these deficits and alterations occur in individuals before or after an initial ankle sprain.…”
mentioning
confidence: 99%
“…These alterations have been hypothesized to play a role in force absorption and production and associated plantar pressure research has identified differences in the center of pressure during gait [68]. Compared to healthy subjects, CAI patients have been found to have a more laterally situated center of pressure during gait [69,70]. More complex analysis of movement has found more sensitive alterations in joint coupling around the ankle [47].…”
Section: Sensorimotor Function and Ankle Instabilitymentioning
confidence: 99%
“…Más autores analizaron las presiones plantares donde sugieren que el grupo con Inestabilidad crónica tiene mayores presiones plantares laterales y ello es un factor que predispone a la inestabilidad lateral 16,17,18 , sin embargo, en un estudio de Huang PY, vieron un cambio del cop de lateral a medial más rápido en pacientes con inestabilidad así como un mayor pico de presión en M1, que suelen ser indicadores de pronación del pie por colapso del arco longitudinal interno. Roel De Ridder, contradice esta distribución de presiones más lateral 16,17,18 en pacientes con Inestabilidad cró-nica 19 y T. Willems et al hallaron mayor presión bajo la zona medial del pie, un retraso en la flexión de rodilla máxima, una resupinación retrasada en la fase de propulsión, un despegue por zona lateral y no por el hallux, un tiempo total de apoyo del pie más largo que el grupo control, un mayor rango de movimiento en 1ª metatarsofalángica 20 , todo ello sugiere un aumento de momentos pronadores. Los factores de riesgo anatómicos que se encuentran asociados a la aparición de un esguince lateral, son principalmente el rango de eversión calcánea en mujeres y el incremento de inclinación del astrágalo en hombres 20 .…”
Section: Introductionunclassified